2006
DOI: 10.1001/archinte.166.17.1855
|View full text |Cite
|
Sign up to set email alerts
|

Physician Communication When Prescribing New Medications

Abstract: When initiating new medications, physicians often fail to communicate critical elements of medication use. This might contribute to misunderstandings about medication directions or necessity and, in turn, lead to patient failure to take medications as directed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
231
6
9

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 340 publications
(254 citation statements)
references
References 40 publications
8
231
6
9
Order By: Relevance
“…al identifiy additional patient and provider level factors predictive of nonadherence to antipsychotic medication among persons with schizophrenia including poor insight, negative attitude or subjective response toward medication, substance abuse, shorter illness duration, and inadequate discharge planning or aftercare environment [14]. Potentially related to language proficiency, a patient’s knowledge regarding benefits of the medication, side effects, and frequency, duration, and dosing may be affected by providers’ explanations for new medications [15]. Similarly, a client’s level of health literacy may affect the processing of information provided during clinical visits [16].…”
Section: Introductionmentioning
confidence: 99%
“…al identifiy additional patient and provider level factors predictive of nonadherence to antipsychotic medication among persons with schizophrenia including poor insight, negative attitude or subjective response toward medication, substance abuse, shorter illness duration, and inadequate discharge planning or aftercare environment [14]. Potentially related to language proficiency, a patient’s knowledge regarding benefits of the medication, side effects, and frequency, duration, and dosing may be affected by providers’ explanations for new medications [15]. Similarly, a client’s level of health literacy may affect the processing of information provided during clinical visits [16].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Tarn et al showed that family and internal medicine physicians mention adverse effects to only 33% of their patients, with a mean medication communication index (MCI) of 3.1/5, indicating that they communicate only 62% of necessary elements of new medications to their patients. 12 Ha et al presents numerous barriers to good communication in the doctor-patient relationship such as deteriorating physician-communication skills, nondisclosure of information such as adverse drug reactions and complications from procedures, doctor-avoidance behavior surrounding difficult topics such as uncertainties in diagnosis and treatment failures, discouragement of collaboration between physicians and patients to create optimal care plans that suit both parties, and resistance by patients to engage in the medical decisionmaking process. 14…”
Section: Misperceptions and Assumptionsmentioning
confidence: 99%
“…In addition to being wasteful and burdening the system with unendurable costs, overuse of medical services comes with its own potential for negative effects on patienthealth such as false-positive tests, procedure-related complications, adverse medication effects, and drugdrug interactions. 5,8,10,12 …”
Section: Viewpoint Room For Improvementmentioning
confidence: 99%
See 1 more Smart Citation
“…[81][82][83] The availability of liquid medications in different concentrations, 84 instructions given using different units of measurement (eg, mL, teaspoon, tablespoon), 85 and the wide variety of dosing instruments 86-88 also contribute to parent confusion with provider instructions. 86,87,89 The literacy demands placed on patients and caregivers as they seek to follow medication instructions are formidable.…”
Section: Patient Safety and Medication Errorsmentioning
confidence: 99%